Encyclopedia of leadership - Goethals, George R.; Sorenson, Georgia Jones; Burns, James MacGregor (Thousand Oaks, Calif. : Sage Publications, 2004)
"The editors' eclectic, interdisciplinary, and global approach goes far beyond the usual literature on management to create a broad foundation for this developing field, drawing concepts and examples from religion, philosophy, business, politics, the arts, and other fields. Entries are often accompanied by sidebars with excerpts from primary texts and by pull quotes with stimulating epigrams. Many articles include extended case studies of leaders ranging from Alexander the Great to Louis B. Mayer."--"Reference that rocks," American Libraries, May 2005.
"A Sage reference publication."
"Appendix 1, Bibliography of significant books on leadership": v. 1, p. A1-A7. This bibliography is repeated in all 4 vols.
Includes bibliographical references and index.
Keywords: Leadership; Leadership